Effects of density on growth, body composition and antioxidant indicators of Perinereis aibuhitensis and total nitrogen in sediments. (16th April 2018) - Lv, Fu; Nie, Qing; Yu, Ye‐Bing; Liu, Fei; Lv, Lin‐Lan; Zhao, Wei‐Hong; Zhang, Gen
Abstract: Perinereis aibuhitensis is a marine polychaete living in intertidal zones that has important economic values. The present study investigated the effects of density on growth, body component and indices of antioxidant status of P. aibuhitensis as well as content of total nitrogen in sediments. When density was above 600 ind/m 2, specific growth rate and protein efficiency ratio both decreased, suggesting that the optimal density ranged from 400 to 600 ind/m 2 . Survivorship and content of crude protein of P. aibuhitensis significantly decreased at densities above 700 ind/m 2 . At densities above 700 ind/m 2, activities of superoxide dismutase (SOD) and catalase (CAT) as well as contents of methane dicarboxylic aldehyde (MDA) were significantly up‐regulated, suggesting oxidative stresses to clamworms, which might explain the reduced survivorship. Moreover, total nitrogen content in sediment per kilogram of P. aibuhitensis significantly increased at density above 600 ind/m 2, suggesting that high density resulted in the extra release of N to the environment, which might pollute the habitats and become toxic to clamworms.